Վարդգես Պետրոսյանը «Գարուն» ամսագրի խմբագիր - Նուրիջանյան, Գոհար (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Журнал «Гарун» («Весна»), основанный В. Петросяном, стал глашатаем передовых идей и рупором писателей-авангардистов. На страницах журнала издавались произведения молодых талантливых армянских писателей постсталинской эпохи. В. Петросян стал основоположником новой публицистической школы, яркими представителями, которой стали публицисты 60-ых гг. XX в. ‒ Марго Гукасян, Армен Оганисян и др. Изданное в «Гаруне» эссе В. Петросяна «Армянские эскизы» наметило новое направление в истории армянской публицистики. The magazine “Garun” (“Spring”), founded by V. Petrosian became a herald of advanced ideas and a trumpet for avant-garde writers. The pages of the magazine were filled with the writings of the young and talented Armenian writers of the post-Stalin epoch. V. Petrosian was the founder of the new school of public writing, brilliant representatives of which in the 60s of the 20th century became such public writers as Margo Ghukasian, Armen Hovhannisian and others. The essay “Armenian Sketches” by V. Petrosian traced out a novel rout in the history of Armenian public writing.
Keywords: Հայագիտություն; Պատմություն